Reduced lactic acidosis risk with Imeglimin: Comparison with Metformin. Issue 5 (11th March 2022) - Theurey, Pierre; Vial, Guillaume; Fontaine, Eric; Monternier, Pierre‐Axel; Fouqueray, Pascale; Bolze, Sébastien; Moller, David E.; Hallakou‐Bozec, Sophie
Abstract: The global prevalence of type 2 diabetes (T2D) is expected to exceed 642 million people by 2040. Metformin is a widely used biguanide T2D therapy, associated with rare but serious events of lactic acidosis, in particular with predisposing conditions (e.g., renal failure or major surgery). Imeglimin, a recently approved drug, is the first in a new class (novel mode of action) of T2D medicines. Although not a biguanide, Imeglimin shares a chemical moiety with Metformin and also modulates mitochondrial complex I activity, a potential mechanism for Metformin‐mediated lactate accumulation. We interrogated the potential for Imeglimin to induce lacticacidosis in relevant animal models and further assessed differences in key mechanisms known for Metformin's effects. In a dog model of major surgery, Metformin or Imeglimin (30–1000 mg/kg) was acutely administered, only Metformin‐induced lactate accumulation and pH decrease leading to lactic acidosis with fatality at the highest dose. Rats with gentamycin‐induced renal insufficiency received Metformin or Imeglimin (50–100 mg/kg/h), only Metformin increased lactatemia and H + concentrations with mortality at higher doses. Plasma levels of Metformin and Imeglimin were similar in both models. Mice were chronically treated with Metformin or Imeglimin 200 mg/kg bid. Only Metformin produced hyperlactatemia after acute intraperitoneal glucose loading. Ex vivo measurements revealed higher mitochondrial complex I inhibition with Metformin versus slight effects with Imeglimin. Another mechanism implicated in Metformin's effects on lactate production was assessed: in isolated rat, liver mitochondria exposed to Imeglimin or Metformin, only Metformin (50–250 µM) inhibited the mitochondrial glycerol‐3‐phosphate dehydrogenase (mGPDH). In liver samples from chronically treated mice, measured mGPDH activity was lower with Metformin versus Imeglimin. These data indicate that the risk of lactic acidosis with Imeglimin treatment may be lower than with Metformin and confirm that the underlying mechanisms of action are distinct, supporting its potential utility for patients with predisposing conditions. Abstract : Imeglimin is a recently launched medicine for type 2 diabetes (2021). Data suggest that the chemical structure and/or some aspects of mode of action may overlap with Metformin. Lactic acidosis risk with Imeglimin, a key concern for Metformin, is thus an important unanswered question. Here, we show that the risk of lactate accumulation and acidosis with Imeglimin treatment is significantly lower than with Metformin, and we confirm that the underlying mechanisms of action are distinct.